Distribution and Determinants of Stunting Prevention Behavior Among Adolescents - Sukamto, Ika Sumiyarsi; Mustika, Dian Nintyasari; Cahyani, Fitria Fahma Nur (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2026)
Background: Stunting remains a persistent public health concern in Indonesia, and adolescence represents a strategic period to prevent its long-term consequences. Understanding sanitation and nutritional behaviors among adolescents is essential because these behaviors contribute to stunting prevention efforts. The purpose of this study is to analyze the distribution and determinants of stunting prevention behavior in adolescents in Sukoharjo district. Methods: This research employed a cross-sectional design to assess the relationship between individual characteristics and stunting prevention behaviors among high school students in Sukoharjo District. Data on knowledge, sanitation behavior, and balanced nutrition behavior were obtained using a validated questionnaire. Because the data were not normally distributed, bivariate analysis using Spearman’s correlation test was performed to examine associations between age, pocket money, BMI, knowledge, and stunting prevention behaviors. Result: Most adolescents demonstrated good sanitation behavior but only moderate nutritional behavior. Although knowledge levels were generally high, knowledge did not translate into improved sanitation or nutrition practices. All correlations between age, pocket money, BMI, or knowledge and sanitation or nutritional behavior were categorized as very weak, with p-values >0.05. Additionally, sanitation behavior did not correlate with nutritional behavior, indicating that these behaviors are shaped by different influencing factors. Conclusions: Individual characteristics and knowledge were not significant predictors of adolescents’ sanitation or nutritional behavior. The absence of meaningful associations suggests that broader social, environmental, and familial influences may play a more dominant role in shaping stunting prevention behaviors. Therefore, interventions should emphasize supportive environments, family engagement, and behavior-oriented strategies rather than relying solely on knowledge-based approaches